FINANCIAL INFORMATION SYSTEM OF CASH FUNDS MANAGEMENT at AL IRSYAD MOSQUE SURABAYA - A. A. Gde Satia Utama; Rafli Farid Basamalah Basamalah (AIBPM Publisher, 2019)
Al Irsyad Mosque of Surabaya as one of the non-profit organization that is structurally under Al Irsyad Surabaya Education Foundation (YPAS) always gives a financial report to the foundation and to the community or congregation. However, financial statements are made quite simple so can not describe the resource usage for each program implemented, and are still difficult to use as a basis for evaluation and decision-making, especially for the control of cash flow. Cash flow at Al Irsyad mosque often is negative, ie the amount of expenditure is greater than the amount of receipt. This leads to the Al Irsyad mosque often lack funds to meet any operational activities. Based on that problem, Al Irsyad Mosque needs to design Financial Information System mosques cash management to increase the loyalty of the mosque to stakeholders. This qualitative research uses the case study method and considered as an exploratory characteristics. The design expected to resolve the problems regarding the availability of financial reports that can help administrators of Al Irsyad mosque in managing cash effectively and efficiently so that it can continuously improve loyalty and funds from donors